OPTIMIZATION OF ROCK PHOSPHATE USE AND EFFECT ON SOYBEAN GRAIN YIELD AND YIELD COMPONENTS ON AN ANDOSOL AND ACRISOL OF CAMEROON - Lawrence T. Nanganoa; Foncha Felix; Kamdem N. Franck Gilles; Djocne F. Christiane; Christopher Suh; Francis A. Ngome (Big Data in Agriculture)
Modulation of rock phosphate fertilizer dose in soybean cultivation is crucial for maximizing plant growth and grain yield while ensuring efficient use of resources and environmental sustainability. This study evaluated rock phosphate (RP) dose to produce soybean on Leptic Andosol in Foumbot and Acrisol in Mbalmayo, respectively in the West and Centre regions of Cameroon. This split-plot experiment consisted of five fertilizer rates (control-no input and four Phosphorus (P) rates of 0, 30, 60 and 90 kg P /ha respectively) and two soybean varieties (TGX 1910-14 F and TGX 2001-24 DM) laid out in randomized complete block design with each treatment replicated three times. Plots containing the different P rates also had N (25 kg / ha) and K (40 kg / ha) straight fertilizers. Analysis of variance showed that fertilizer application significantly increased (P < 0.01) the number of pods and seeds, aboveground dry weight, and grain yield of the soybean varieties at both locations. There was an outright grain yield and economic benefit because of fertilizer application which increased with addition of phosphorus in the fertilizer mixtures. The grain yield response to phosphorus fertilizer was fitted to quadratic and square root models. The two models predicted maximum yields which were close to the experimental maximums recorded at P rates of 30 kg / ha (TGX 2001-24 DM: 5.04 and 4.89 t / ha) and 60 kg / ha (TGX 1910-14 F: 4.72 and 4.38 t / ha) at Foumbot and Mbalmayo respectively. The average optimum P fertilizer recommendations for soybean estimated by square root model (29.41 kg P/ ha) was considerably lower than that given by the quadratic equation (45.61 kg P/ ha) for both sites but only slightly lower the experimental dose of 30 kg P/ ha. Taking into account the yield and cost benefit analysis of the soybean seeds, fertilization with 30 kg P/ ha can be recommended.